Antagonistic Activity of Trichoderma spp. Against Fusarium oxysporum in Rhizosphere of Radix pseudostellariae Triggers the Expression of Host Defense Genes and Improves Its Growth Under Long-Term Monoculture System - Chen, Jun; Zhou, Liuting; Din, Israr Ud; Arafat, Yasir; Li, Qian; Wang, Juanying; Wu, Tingting; Wu, Linkun; Wu, Hongmiao; Qin, Xianjin; Pokhrel, Ganga Raj; Lin, Sheng; et al. (Frontiers in Microbiology, 2021)
Under consecutive monoculture, the abundance of pathogenic fungi such as Fusarium oxysporum in the rhizosphere of Radix pseudostellariae, negatively affect the yield and quality of the plant. Therefore, it is pertinent to explore the role of antagonistic fungi for the management of fungal pathogens such as F. oxysporum. Our PCR-DGGE results revealed that the diversity of Trichoderma spp. was significantly declined due to extended monoculture. Similarly, quantitative PCR analysis showed a decline in Trichoderma spp. whereas a significant increase was observed in F. oxysporum. Furthermore, seven Trichoderma isolates from the R. pseudostellariae rhizosphere were identified and evaluated in vitro for their potentiality to antagonize F. oxysporum. The highest and lowest percentage of inhibition (PI) observed among these isolates was 47.91% and 16.67% respectively. In in vivo assays, the R. pseudostellariae treated with four Trichoderma isolates, having PI > 30%, were used to evaluate the biocontrol efficiency against F. oxysporum in which T. harzianum ZC51 enhanced the growth of the plant without displaying any disease symptoms. Furthermore, the expression of eight defense-related genes of R. pseudostellariae in response with combination of F. oxysporum and T. harzianum ZC51 treatment were checked and most of these defense genes were found to be upregulated. In conclusion, this study reveals that the extended monoculture of R. pseudostellariae could alter the Trichoderma communities in the plant rhizosphere leading to relatively low level of antagonistic microorganisms. However, T. harzianum ZC51 could inhibit the pathogenic F. oxysporum and induce the expression of R. pseudostellariae defense genes. Hence T. harzianum ZC51 improves the plant resistance and reduces the growth inhibitory effect of consecutive monoculture problem.